PARTISIPASI KELOMPOK PEREMPUAN DALAM AKSES DAN PROGRAM SANITASI DI KABUPATEN LOMBOK TENGAH DAN MANGGARAI BARAT - Savitri, I Gusti Ayu Devi; Dwipayanti, Ni Made Utami (ARCHIVE OF COMMUNITY HEALTH, 2023)
Most Indonesian people still do not have proper sanitation access and behavior. Therefore, the government held the STBM (Community-Based Total Sanitation) Program. However, in the course of the STBM program there is still a gender gap in both the decision-making process and the availability of special facilities for women. The aim of the research is to analyze the things that support and hinder the participation of women's groups in sanitation access and programs in Central Lombok and West Manggarai districts. This study used qualitative research methods. The research sample was taken using a purposive sampling technique with a total of 39 FGD participants who were divided into 6 FGD groups. Data was collected using Focus Group Discussion. Data were analyzed using Thematic Analysis. The results show that the participation of women's groups in the household is high, while the participation of women's groups in the community is still low. Therefore, support is needed to increase the involvement of women's groups in efforts to fulfill access and sanitation programs Keyword : STBM GESI, Women's Participation, Sustainable Sanitation